Restoration of the Ellipsoid Zone and Visual Prognosis at 1 Year after Surgical Macular Hole Closure - Hiruma Hasebe; Naoki Matsuoka; Hiroko Terashima; Ryo Sasaki; Eriko Ueda; Takeo Fukuchi (Journal of Ophthalmology)
Purpose. To evaluate the restoration of the ellipsoid zone (EZ) and its influence on visual prognosis 1 year after surgical macular hole (MH) closure. Method. Subjects were patients with stage 2, 3, or 4 idiopathic MH who underwent primary vitrectomy that resulted in successful hole closure. Nineteen eyes with both EZ disruption with foveal detachment and a continuous external limiting membrane on optical coherence tomography during the early postoperative period were included in this study. Result. EZ disruption was restored in 10 eyes (53%, Group A) and remained in 9 eyes (47%, Group B) at 1 year after surgery. In Group B, the diameter of the residual EZ disruption was 54.7±33.1 μm. LogMAR visual acuity (VA) 1 year after surgery was significantly better than preoperative VA in each group (Group A: -0.007±0.102; P<0.001; Group B: 0.051±0.148; P<0.001), but there was no significant difference between the 2 groups (P=0.332). There was no significant correlation between logMAR VA and EZ disruption diameter at 1 year after surgery. Conclusion. EZ was restored in 53% of eyes at 1 year after surgical closure of idiopathic MH. Mean residual EZ disruption diameter was 54.7±33.1 μm. Neither resolved nor residual EZ disruption influenced postoperative VA.